Numerology : [a beginner's guide to the power of numbers] - Simpson, Jean, 1942- (Awakened life (Alpha (Firm)), 2023)
Uncover the secrets to your happiness and success! Numerology takes two key pieces of information, specific to you and only you, and opens up captivating pathways of insight and self-awareness into who you are, where you've been and where you're going. With a few easy calculations, you can discover exactly what the Universe has planned for you. In this alluring guide, you'll find: An exploration of what numerology is and what it can do for you; A fascinating look at the meaning of your birthday; Easy lessons for calculating and understanding your Destiny, Soul, and Personality numbers ; Tips for predicting and identifying important years and periods in your life ; Fun suggestions for choosing important names and dates, even children's names ; An easy-to-use worksheet for calculating and organizing all your numbers.